Linear and change of direction repeated sprint ability tests: a systematic review - Kyles, A.; Oliver, J. L.; Cahill, M. J.; Lloyd, R. S.; Pedley, J. (The Journal of Strength and Conditioning Research, 2023)
The ability to repeatedly sprint is important in many sports, but there is no established protocol for measuring repeated sprint ability (RSA). The purpose of this review was to identify overground RSA protocols previously reported in the literature and to recommend standardized protocols. A systematic review of the literature was used to identify studies that have used an RSA test, with data describing protocol design extracted. One hundred eight studies were included in the review, across which 47 unique protocols were identified. Eighteen protocols included at least one change of direction (COD), and this increased mean sprint time compared with linear RSA tests (7.26 ± 1.84 vs. 4.48 ± 1.02 seconds). There was considerable variability across protocols regarding sprint distance (20-40 m), sprint repetitions (3-15), recovery duration (10-60 seconds), recovery type (active vs. passive), and work-to-rest ratio (=1:1.4-19.2). Separate protocols are needed for linear and COD tests, and these should reflect the brief nature of intense periods of competition and stress the ability to recover. Based on data across studies for protocol design and to ensure a demanding work-to-rest ratio, it is suggested that a linear RSA should comprise 6 × 30 m sprints separated by 15 seconds of active recovery. To provide some parity to linear tests, to keep work duration brief and to maintain a demanding work-to-rest ratio, a COD RSA should comprise 6 × 30 m shuttle sprints (15 + 15 m), providing one change of direction (180° COD), and maintaining a 15-second active recovery.